The Great Pagoda at Kew: Colour and Technical Innovation in Chinoiserie Architecture. (2019) - Prosser, Lee
Abstract: The Great Pagoda in Kew Gardens is the most important surviving chinoiserie building in Europe. Restoration of the building in 2017–18 was attended by extensive documentary and forensic research, which revealed two markedly different eighteenth-century schemes of decoration undertaken by the architect William Chambers in 1761 and 1784. Both schemes were characterised by the use of innovative and experimental building materials and the application of a varied colour palette which can be shown to have close affinities with temporary, ephemeral buildings. With so few surviving contemporary examples for reference, colour and building materials appear as important characteristics of chinoiserie architecture. The discoveries at Kew demonstrate that these elements were fundamental to the style, which was never constrained by any fixed set of rules. Chambers drew on no single source for the building, but instead imaginatively adapted the Chinese style in a structure of great virtuosity.